Propagation prediction techniques and antenna modeling (150 to 1705kHz) for intelligent transportation systems (ITS) broadcast applications. - DeMinco, Nicholas
This paper discusses the basic aspects of radio-wave propagation and antenna modeling at 150 to 1705 kHz. The paper contains descriptions of both sky-wave and ground-wave propagation-prediction models, in addition to the methodology used to analyze antennas that operate in this band. A method of calculating and normalizing antenna gain for system computations is also discussed. The sky-wave models described in this paper are valid from 150 to 1705 kHz. The ground-wave models described in this paper are valid from 10 kHz to 30 MHz. The propagation of radio waves from 150 to 1705 kHz includes both a ground wave and a sky wave, and is quite different from propagation at any other frequency. The methods used for antenna modeling and analysis in this band are also quite unlike those in other bands. The AM broadcast band of 535 to 1605 kHz is planned to be used in the advanced traveler information systems (ATIS) of intelligent transportation systems (ITS), to provide information such as road conditions, road hazards, weather, and incident reporting for rural travelers. The band of frequencies from 285 to 325 kHz is presently being used in another application of ITS, called the Differential Global Positioning System (DGPS), which will be used for precision location of vehicles. The propagation-prediction models and antenna-analysis methods described here can be used for designing systems and making performance predictions for both of these ITS applications, or for any other systems that operate in this band of frequencies from 150 to 1705 kHz. Some examples of comparisons of measured and predicted data are also presented. A computer program that includes all of these propagation-prediction models and antenna-modeling techniques was used.
Keywords: Radio propagation; Antennas; Radio communication; Radio broadcasting; Navigation; Diffraction; Refraction; Ground wave propagation